2015
DOI: 10.3945/ajcn.114.092288
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cardiovascular risk factor–related dietary patterns with reduced rank regression and random forest in the EPIC-NL cohort

Abstract: Including risk factors in RRR and RF-CTA resulted in small differences in food groups, contributing to similar patterns that showed in general stronger associations with CAD than PCA and KCA, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 33 publications
5
26
0
Order By: Relevance
“…Similar comparison studies also showed that in general PCA-derived patterns explain more variance of the food groups but explain less of the variance in response variables (Hoffmann et al 2005;Hoffmann et al 2004). Our first RRR pattern explained 40.5% of the response variable variation, which is in line with results from other studies (Biesbroek et al 2015;Hoffmann et al 2005;Hoffmann et al 2004), but clearly leaves a proportion of the variance unexplained. Other factors, such as socioeconomic status, age, or gender might also impact GHG emissions of the diet and dietary quality.…”
Section: Discussionsupporting
confidence: 80%
“…Similar comparison studies also showed that in general PCA-derived patterns explain more variance of the food groups but explain less of the variance in response variables (Hoffmann et al 2005;Hoffmann et al 2004). Our first RRR pattern explained 40.5% of the response variable variation, which is in line with results from other studies (Biesbroek et al 2015;Hoffmann et al 2005;Hoffmann et al 2004), but clearly leaves a proportion of the variance unexplained. Other factors, such as socioeconomic status, age, or gender might also impact GHG emissions of the diet and dietary quality.…”
Section: Discussionsupporting
confidence: 80%
“…The relationships between selected health outcomes and 'traditional' DP identified in different populations strongly depend on the dietary habits of these populations. For instance, in the European Prospective Investigation into Cancer (EPIC) -Netherlands Study, the 'traditional' DP was significantly associated with coronary heart disease (hazard ratio (HR) 1.25; 95% CI: 1.07-1.47 or 1.29; 95% CI: 1.11-1.50, depending on the statistical method) [26]. In a cross-sectional study performed in Brazil, the 'traditional' DP had a negative effect on obesity indicators, lipids and fasting plasma glucose [27].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, in contrast to purely data-driven approaches, such as PCA, RRR can explain variation in nutrient intakes by linear functions of food intakes ( 5 ) . Taken together, RRR generates DP that may be more appropriate for the diseases of interest ( 7 ) . Although DP generated from RRR are specific to the dietary intakes of the cohort, and are thus criticised for their generalisability when compared with diet quality scores, RRR has the advantage of being less sensitive to violations of assumptions concerning directional relations because it does not fix expected directions of effects when determining response variables ( 5 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The latter offers the advantage of considering the correlation structure of food intakes, yet often fails to predict disease outcomes ( 4 ) . Reduced rank regression (RRR) is a combined approach that utilises both exploratory, data-driven analyses and a priori knowledge of a disease ( 5 ) , which has been shown to derive DP that predict disease outcomes ( 6 , 7 ) . Moreover, unlike purely data-driven approaches such as principal component analysis (PCA), RRR provides a valuable link between nutrient and food-based approaches ( 8 ) .…”
mentioning
confidence: 99%